Kropotkin - o explorador: o apoio mútuo como fator de evolução - Ítalo Barbosa Lima Siqueira (Universidade Federal do Amazonas, 2016)
In the bicentenary year of Darwin's birth, thinking of the work O Mutual Support (1902), the observations and thinking of Peter Kropotkin, one of the many marginalized authors in the social and human sciences, becomes important due to his numerous theoretical contributions as a scientist and as an anarchist, who thinks of a complex methodology to overcome capitalism. When Thomas Henry Huxley claims that conflict is not only desirable as one of the conditions of progress, and thus inevitable, Kropotkin proposed to discuss the matter, giving his own interpretation of Darwin's evolutionary theory. His series of essays then made in a famous newspaper, culminated in his work O Apoio Mútuo (1902), where he opposes social Darwinism, stating that mutual support between species is the most important element in its evolution.